2016
DOI: 10.3390/ijms17060976
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobacterial Strain Bacillus megaterium BOFC15 Induces Cellular Polyamine Changes that Improve Plant Growth and Drought Resistance

Abstract: Plant-growth-promoting rhizobacteria can improve plant growth, development, and stress adaptation. However, the underlying mechanisms are still largely unclear. We investigated the effects of Bacillus megaterium BOFC15 on Arabidopsis plants. BOFC15 produced and secreted spermidine (Spd), a type of polyamine (PA) that plays an important role in plant growth. Moreover, BOFC15 induced changes in the cellular PAs of plants that promoted an increase of free Spd and spermine levels. However, these effects were remar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(105 citation statements)
references
References 59 publications
2
99
0
4
Order By: Relevance
“…phytobeneficialis MSR2 contains multiple genes involved in the biosynthesis and transport of polyamines such as putrescine, spermidine, 1,3‐diaminopropane, as well as genes involved in the biosynthesis and catabolism of GABA (Table S14). Polyamines and GABA play an important role in plant–microbe interactions and plant growth promotion activities of plant‐associated bacteria (Xie et al ., ; Bown and Shelp, ; Zhou et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…phytobeneficialis MSR2 contains multiple genes involved in the biosynthesis and transport of polyamines such as putrescine, spermidine, 1,3‐diaminopropane, as well as genes involved in the biosynthesis and catabolism of GABA (Table S14). Polyamines and GABA play an important role in plant–microbe interactions and plant growth promotion activities of plant‐associated bacteria (Xie et al ., ; Bown and Shelp, ; Zhou et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Polyamines and GABA play an important role in plantmicrobe interactions and plant growth promotion activities of plant-associated bacteria (Xie et al, 2014;Bown and Shelp, 2016;Zhou et al, 2016).…”
Section: Phosphate Solubilization and Phosphorus Acquisitionmentioning
confidence: 99%
“…It has previously been reported that polyamine can stimulate the biosynthesis of NO in Arabidopsis roots [35]. Furthermore, interruption of NO release has been shown to inhibit certain effects of polyamine on plants [36,50], indicating that NO acts as a downstream transducer of polyamine-mediated signaling pathways. Intriguingly, overproduction of NO can provoke toxic effects in plants [51].…”
Section: Discussionmentioning
confidence: 99%
“…Other microbial products, such as trehalose and polyamines, could also be important to both microbe and root cell survival. Secretion of the polyamine spermidine by a PGPR Bacillus isolate is instrumental in the induction of drought tolerance in the plant host (Zhou et al, 2017). Although a role in drought tolerance awaits investigation, polyamine synthesis by P. chlororaphis O6 is linked to its biocontrol potential (Park et al, 2017).…”
Section: Biofilm Formation and Relevance To Drought Tolerancementioning
confidence: 99%